Optoelectronic properties in CuO nanofibers, pure and doped with Mn - M. Piñón Espitia; J.A. Duarte-Moller; J.A. López-Gallardo; M.T. Ochoa-Lara (Results in Physics)
This research presents an optoelectronic study based on the dielectric function obtained from Kramers-Kronig analysis of CuO nanofibers (NFs), both pure (A) and 2.5 % Mn-doped (B), synthesized via the electrospinning method. The NFs were characterized using XRD and STEM, with a specific focus on analyzing valence electron energy loss (VEELS). This analysis was complemented by Cole-Cole diagrams to determine the band gap (Eg) and compare it with the EELS results. These properties reveal that the materials exhibit a semi-metallic nature due to the band gaps of 2.03 eV (A-NFs) and 2.85 eV (B-NFs), as well as negative conductivity in the dielectric function, and holes in the conduction band.